3D heterostructure of 2D Y-doped Cu(OH)2 nanosheet supported by nickel foam as advanced electrodes for high performance supercapacitor. (May 2021) - Liu, He; An, Shengli; Han, Xiaoxing; Sun, Xuejiao; Cui, Jinlong; Zhang, Yongqiang; He, Wenxiu
Abstract: Herein, the 3D structure of 2D Y-doped Cu(OH)2 nanosheet supported by nickel foam was successfully synthesized by simple solvent thermal reaction. Interwoven nanosheet structures are anchored to the nickel foam skeleton, which makes full use of its electrochemical active sites and speeds up ion and electron transport. Meanwhile, Y-doped can also improve the inherent conductivity of Cu(OH)2 electrode materials. According to the electrochemical test, the specific capacitance of Y-doped Cu(OH)2 /NF was 2775 F/g at 1A/g, which shows good charge and discharge rate and cycling stability (86.2% retention over 6000 cycles). In addition, the Y-doped Cu(OH)2 /NF//AC device also provides good specific capacitance (192.53 F/g at 1A/g) and has an energy density of 60.16 Wh/kg at a power density of 749.98 W/kg. Highlights: Electrode materialsis facilely prepared by simple solvent thermal reaction. The introduction of Yttrium ion contributes to good electrochemical performance. Nickel foam can be directly used as an electrode to optimize electrochemical performance.